2004
DOI: 10.22358/jafs/67630/2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics and selenium combination on the immune and blood cholesterol concentration of pigs

Abstract: Ninety-six weanling piglets (four weeks old) were randomly assigned into four treatments as follows: 1. control group, 2. probiotics group, 3. probiotics combined with 0.3 ppm organic selenium and 4. carbadox group. Collected data was analysed by using the GLM program of SAS (1990), and each of the two groups was compared using Duncan's test, while the GLM analysis was significant.The experimental results revealed no influence on pig growth performance by the addition of probiotics alone or with the selenium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
2
4
1
Order By: Relevance
“…These results are in accordance with results of Yu et al (2004). Yu and his co-authors evaluated the effect of probiotics and selenium combination on the immune and blood cholesterol concentration of pig.…”
Section: Treatmentssupporting
confidence: 91%
“…These results are in accordance with results of Yu et al (2004). Yu and his co-authors evaluated the effect of probiotics and selenium combination on the immune and blood cholesterol concentration of pig.…”
Section: Treatmentssupporting
confidence: 91%
“…The present study stated that, there was an increasing tendency of HDL after probiotic treatment. These results are in accordance with results of Yu et al (2004) who found 179 mg/dl of HDL concentration in blood after supplementation with direct fed microbes in cows. After probiotic treatment, HDL (good cholesterol) was significantly increased which is good for animal health status.…”
Section: Discussionsupporting
confidence: 93%
“…Reduction of the total level of cholesterol and triglycerides was obtained in the blood of rabbits receiving a high-fat diet using 1 ppm sodium selenite [Kang et al 2000]. However, in the study in piglets, Yu et al [2004], using 0.3 ppm organic selenium, showed a trend to lower total cholesterol and increase HDL cholesterol, which was not confirmed in this study. Guo et al [2020] in the study carried out on mice suggest that selenium in the form of nanoparticles can significantly alleviate hyperlipidemia.…”
Section: Discussioncontrasting
confidence: 65%